History and Theory in Anthropology - Barnard, Alan. ([S.l.] : Cambridge University Press, 2000)
Anthropology is a discipline very conscious of its history. Alan Barnard has written a clear, detailed overview of anthropological theory that brings out the historical contexts of the great debates, tracing the genealogies of theories and schools of thought. His book covers the precursors of anthropology; evolutionism in all its guises; diffusionism and culture area theories, functionalism and structural-functionalism; action-centered theories; processual and Marxist perspectives; the many faces of relativism, structuralism and poststructuralism; and recent interpretive and postmodernist viewpoints. This is a balanced and judicious survey, which also considers the problems involved in assessing anthropological theories.
Keywords: Anthropology; Anthropology--Philosophy